PENGARUH BRAND IMAGE, DIGITAL MARKETING, DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA DI KABUPATEN BANGKA BARAT - Astri Febrianti; Rita Deseria; Nadia Sri Rezeki; Efendi Efendi (LPPM STIE PERTIBA Pangkalpinang, 2023)
This study aims to analyze the influence of brand image, digital marketing, and influencer marketing on purchasing decisions for Yamaha motorcycles in West Bangka Regency. This study uses an explanatory research approach which explains the causal relationship (cause and effect) between variables. The research model is hypothesis testing, which tests the theoretical relationships built by the author. The data used were collected from research respondents, namely consumers/users of Yamaha motorcycles in West Bangka Regency. The data analysis technique used multiple linear regression analysis. The results of this study show that the results of the F test calculation state that the brand image, digital marketing and influencer marketing variables together have a significant effect on purchasing decisions for Yamaha motorcycles in West Bangka Regency. Based on the results of the t test, it is stated that the three variables, namely brand image, digital marketing and influencer marketing, have a significant effect on purchasing decisions for Yamaha motorcycles in West Bangka Regency.